Is Information Asymmetry a Disruptive Factor in Food Consumer Behavior During the COVID Pandemic? - Socoliuc, Marian; Grosu, Veronica; Ciubotariu, Marius-Sorin; Brînzaru, Simona-Maria; Cosmulese, Cristina Gabriela (Frontiers in Nutrition, 2022)
Today, food quality and safety, on the one hand, as well as increasing the level of information of consumers with direct implications on their food preferences, on the other hand, are highly debated topics in both national and international literature. The lack of consumers’ knowledge of information on food safety could make consumers purchase unsafe food. In the event of the existence of this kind of information, the consumption would be a safer one. Our research aimed to understand the means of adjusting the food offered to the request manifested by young and educated people and the impact of the information asymmetry on the consumers’ behavior. The main objectives of the study focus on exploring the nature of the informational asymmetry and the extent to which it usually affects the consumers’ perception and on identifying the prevalent socioeconomic factors that influence the consumers’ behavior regarding their perception of the quality of the food products and quantifying the impact of the information asymmetry on consumers’ behavior. In this study, a questionnaire survey among 529 young and educated people was used to design a cumulative analysis in order to allow the forecast based on a future trend of the food policies in relation to the change in the consumers’ behavior induced by the informational asymmetry. This analysis was segmented into impact sections that delineate the weight of the generating asymmetry factors from the weight of the factors with resistance to this phenomenon. The results of the survey led both to the identification of a quantification model of the information asymmetry that manifests itself within the relationship between the producer and the consumer and to the identification of a typology of informational asymmetry which manifests itself differently depending on the features of the food products. The study can be useful for those entities that want to identify the changes in the typology of consumption according to certain criteria in order to correlate their offer with the consumers’ requirements, as well as for the national or regional institutional bodies with a role in developing food policies adapted to these requirements.